Answer:
Step-by-step explanation:
the answer is x<0
because
x-4+4<-4+4
Answer:
Step-by-step explanation:
Subtraction is not commutative. For example, 4 − 7 does not have the same difference as 7 − 4. The − sign here means subtraction.
However, recall that 4 − 7 can be rewritten as 4 + (−7), since subtracting a number is the same as adding its opposite. Applying the commutative property for addition here, you can say that 4 + (−7) is the same as (−7) + 4. Notice how this expression is very different than 7 – 4.
Answer:
45
Step-by-step explanation:
Two tangents drawn to a circle from an outside point form arcs and an angle, and this formula shows the relation between the angle and the two arcs.
m<EYL = (1/2)(m(arc)EVL - m(arc)EHL) Eq. 1
The sum of the angle measures of the two arcs is the angle measure of the entire circle, 360 deg.
m(arc)EVL + m(arc)EHL = 360
m(arc)EVL = 360 - m(arc)EHL Eq. 2
We are given this:
m<EYL = (1/3)m(arc)EHL Eq. 3
Substitute equations 2 and 3 into equation 1.
(1/3)m(arc)EHL = (1/2)[(360 - m(arc)EHL) - m(arc)EHL]
Now we have a single unknown, m(arc)EHL, so we solve for it.
2m(arc)EHL = 3[360 - m(arc)EHL - m(arc)EHL]
2m(arc)EHL = 1080 - 6m(arc)EHL
8m(arc)EHL = 1080
m(arc)EHL = 135
Substitute the arc measure just found in Equation 3.
m<EYL = (1/3)m(arc)EHL
m<EYL = (1/3)(135)
m<EYL = 45
27 * 35
= 20*35 + 7 * 35
= 700 + 245
= 945